2020
DOI: 10.1111/evo.14078
|View full text |Cite
|
Sign up to set email alerts
|

The complex effects of mass extinctions on morphological disparity

Abstract: Studies of biodiversity through deep time have been a staple for biologists and paleontologists for over 60 years. Investigations of species richness (diversity) revealed that at least five mass extinctions punctuated the last half billion years, each seeing the rapid demise of a large proportion of contemporary taxa. In contrast to diversity, the response of morphological diversity (disparity) to mass extinctions is unclear. Generally, diversity and disparity are decoupled, such that diversity may decline as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 85 publications
(196 reference statements)
1
26
0
1
Order By: Relevance
“…At first glance, this contrasts strongly with many previous studies for varied groups that have indicated that taxonomic and morphological diversity were decoupled (e.g. Wills et al, 1994;Fortey et al, 1996;Bapst et al, 2012;Marx and Fordyce, 2015;Puttick et al, 2020), with diversity often expanding or remaining high despite relatively low disparity (Benson et al, 2012;Ruta et al, 2013). However, these studies largely examined variance or range metrics, which-as discussed-are more likely to be affected by outliers.…”
Section: Disparity Patterns and Taxonomic Diversitymentioning
confidence: 63%
See 1 more Smart Citation
“…At first glance, this contrasts strongly with many previous studies for varied groups that have indicated that taxonomic and morphological diversity were decoupled (e.g. Wills et al, 1994;Fortey et al, 1996;Bapst et al, 2012;Marx and Fordyce, 2015;Puttick et al, 2020), with diversity often expanding or remaining high despite relatively low disparity (Benson et al, 2012;Ruta et al, 2013). However, these studies largely examined variance or range metrics, which-as discussed-are more likely to be affected by outliers.…”
Section: Disparity Patterns and Taxonomic Diversitymentioning
confidence: 63%
“…At smaller temporal scales (sometimes considered adaptive radiations sensu stricto -Schluter 2000), they have given rise to groups of highly varied but closely related taxa exquisitely adapted to particular niches (Pinto et al, 2008;Abzhanov 2010), with the adaptive radiation of Geospiza finches having famously aided Darwin in formulating the theory of evolution by natural selection (Abzhanov 2010). Studying the dynamics of these events allows us to better understand the process of evolution and the generation of biodiversity itself, addressing questions such as how long after an adaptive radiation morphological diversity (i.e., disparity) tends to become saturated (Hughes et al, 2013), the correlation of morphological disparity with taxic diversity (Ruta et al, 2013;Puttick et al, 2020), whether elevated rates of evolution occur and how long they last (Puttick, 2018;Hernández-Hernández, 2019), the relative importance of competitive-and non-competitive processes in diversification (Brusatte et al, 2008a;Benson et al, 2014), and the underlying reasons for the success and radiation of particular lineages (Seehausen, 2006;Jønsson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…would be undetectable even if it were present. Moreover, empirical 44 and simulation studies 45 demonstrate that levels of disparity can be maintained in the face of even severe diversity loss, provided extinction is not centrifugal (i.e., preferentially concentrated away from the centre of morphospace).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple disparity indices have been developed to capture different aspects of trait distributions; as a result, consideration of multiple indices is necessary to fully characterize changes in disparity (37,60), especially over mass extinction events (39). We quantified morphological and ecological disparity using three standard indices, which were chosen to capture different aspects of disparity: SOR, which reflects the total amount of morphospace/ecospace occupied in a given time bin; SOV, which provides a measure of dispersion of taxa around the centroid of the group; and shift in centroid, which measures change in the position of taxa within morphospace/ecospace independent of SOR and SOV [for further interpretations of disparity indices, see (7,(60)(61)(62)].…”
Section: Analysis Of Morphological and Ecological Disparitymentioning
confidence: 99%